Meeting between the Prime Minister and representatives of the Miners' Federation of Great Britain and Mining Association (verbatim report) : (1926/04/23) - Mining Association of Great Britain ; Miners' Federation of Great Britain ; Baldwin, Stanley Baldwin, Earl, 1867-1947
23 April 1926